In vivo mutation of pre‐mRNA processing factor 8 (Prpf8) affects transcript splicing, cell survival and myeloid differentiation. Issue 14 (25th May 2013) - Keightley, Maria-Cristina; Crowhurst, Meredith O.; Layton, Judith E.; Beilharz, Traude; Markmiller, Sebastian; Varma, Sony; Hogan, Benjamin M.; de Jong-Curtain, Tanya A.; Heath, Joan K.; Lieschke, Graham J.
Abstract : Mutated spliceosome components are recurrently being associated with perturbed tissue development and disease pathogenesis. Cephalophŏnus ( cph ), is a zebrafish mutant carrying an early premature STOP codon in the spliceosome component Prpf8 (pre‐mRNA processing factor 8). Cph initially develops normally, but then develops widespread cell death, especially in neurons, and is embryonic lethal. Cph mutants accumulate aberrantly spliced transcripts retaining both U2‐ and U12‐type introns. Within early haematopoiesis, myeloid differentiation is impaired, suggesting Prpf8 is required for haematopoietic development. Cph provides an animal model for zygotic PRPF8 dysfunction diseases and for evaluating therapeutic interventions. Abstract : Cephalophoˇnus ( cph ) is a zebrafish mutant in the spliceosome component Prpf8. cph displays U2 and U12 splicing defects and is a model of PRPF8 dysfunction in vivo. The pleiotropic cph phenotype includes neural cell degeneration by apoptosis. cph myeloid deficiencies point to a lineage requirement for zygotic Prpf8.